Concept Development and Design of a Flexible Metallic Wheel with an Adaptive Mechanism for Soft Planetary Soils - Grimm, Christian (2011)
Within the RIMRES project, a modular reconfigurable multi-robot system is being developed, which should demonstrate key technologies required for the exploration of challenging and difficult planetary terrain, as it is found at the lunar south pole. For this purpose, key technologies in the area of autonomy, navigation and locomotion are being investigated and hardware engineered with the overall aim of having a system with interchangeable but compatible components, connected via unique mechanical and electrical interfaces. This thesis was written in close collaboration with the German Aerospace Centre (DLR) at the Institute of Space Systems in Bremen and deals with the concept development and design of a flexible metal wheel with an adaptive mechanism for soft planetary soils. The concept presented here builds upon the DLR wheel design developed for the ESA ExoMars mission, which incorporated flexible metal spokes to enlarge the wheels ground contact area. The new wheel design will be equipped with an intelligent sensor system to monitor and characterise soil properties. Dependent upon whether the rover is rolling over a hard or soft soil area, an integrated adaptable stiffness mechanism will then actively adjust the wheels flexibility. Equivalent to the inflation of a rubber tyre, by increasing the stiffness of the wheel the rolling resistance can be minimised when running on hard ground, whilst decreasing the wheels stiffness will maximise the tractive force when running over soft ground. The work of this thesis in particular, deals with the concept development of such an adaptable system. The previous investigated ideas have been analysed in detail leading to a better understanding of their working principles. Subsequently, a new flexible wheel design was proposed based on the tensioned spoke wheel (bicycle wheel). With the help of computer based finite element analysis the non-linear deformation behaviour of the flexible elements was then evaluated. It has been shown, that the new wheel design, with ...